Pragmatic Language Disorder in Parkinson’s Disease and the Potential Effect of Cognitive Reserve - Montemurro, Sonia; Mondini, Sara; Signorini, Matteo; Marchetto, Anna; Bambini, Valentina; Arcara, Giorgio (Frontiers in Psychology, 2019)
It is known that patients with Parkinson’s disease (PD) may show deficits in several areas of cognition, including speech and language abilities. One domain of particular interest is pragmatics, which refers to the capacity of using language in context for a successful communication. Several studies showed that some specific aspects of pragmatics - both in production and in comprehension - are impaired in patients with PD. However, a clear picture of pragmatic abilities in PD is still missing, as most of the existing studies focused on some specific aspects rather than on sketching a complete profile. Moreover, little is known on the potential role of protective factors in compensating the decline of communicative skills as the disease progresses. The present study has two aims: 1) to provide a complete picture of pragmatic abilities in patients with PD, by using a comprehensive battery (Assessment of Pragmatic Abilities and Cognitive Substrates, APACS) and by investigating the relationship with other aspects of cognitive functioning (e.g., working memory and Theory of Mind); 2) to investigate whether Cognitive Reserve, i.e., the resilience to cognitive impairment provided by life experiences and activities, may compensate for the progressive pragmatic deficits of PD. We found that patients with PD, compared to healthy matched controls, had worse performance in discourse production and in the description of scenes, and that these impairments were correlated with the severity of motor impairment, suggesting a lack of intentionality to communicate. Patients with PD showed also an impairment in comprehending texts and humor, suggesting a problem in inferring from stories. This impairment was related to general cognitive impairment. Notably, we did not find significant difference between patients and controls in figurative language comprehension, a domain that is commonly impaired in other neurodegenerative diseases. This might be indicative of a specific profile of pragmatic impairment in patients with PD, worth of further investigation. Finally, Cognitive Reserve measures showed a high degree of association with pragmatic comprehension abilities, suggesting that the modification of life-styles could be a good candidate for compensating the possible problems in understanding the pragmatic aspects of language, experienced by patients with PD.